Early COPD Diagnosis in Family Medicine Practice: How to Implement Spirometry?. (2nd April 2014) - Saad, Nathalie; Sedeno, Maria; Metz, Katrina; Bourbeau, Jean
Abstract : Introduction . COPD is often diagnosed at an advanced stage because symptoms go unrecognized. Furthermore, spirometry is often not done. Methods . Study was conducted in diverse family medicine practice settings. Patients were targeted if respiratory symptoms were present. Patients had a spirometry to confirm the presence of airflow obstruction and COPD diagnosis. An evaluation of the process was done to better understand facilitating/limiting factors to the implementation of a primary care based spirometry program. Results . 12 of 19 primary care offices participated. 196 of 246 (80%) patients targeted based on the presence of smoking and respiratory symptoms did not have COPD; 18 (7%) and 32 (13%) had COPD, respectively, GOLD I and ≥II. There was no difference in the type and number of respiratory symptoms between non-COPD and COPD patients. Most of the clinics did not have access to a trained healthcare professional to accomplish spirometry. They agreed that giving access to a trained healthcare professional was the easiest and most reliable way of doing spirometry. Conclusion . Spirometry, a simple test, is recommended in guidelines to make the diagnosis of COPD. The lack of allocated time and training of healthcare professionals makes its implementation challenging in family medicine practices.